Large intracoronary thrombi with good TIMI flow during acute myocardial infarction: four cases of successful aggressive medical management in patients without angiographically detectable coronary atherosclerosis. Issue 5 (1st November 2002) - Burzotta, F; Hamon, M; Sabatier, R; Prati, F; Boccanelli, A; Grollier, G
Abstract : Four cases of young patients with acute myocardial infarction are discussed in which urgent angiography showed large intracoronary thrombus and TIMI (thrombolysis in myocardial infarction) flow ≥ 2 in the infarct related artery. The rest of the coronary tree appeared to be free of detectable atherosclerosis. Percutaneous transluminal coronary angioplasty was not performed and an aggressive antiplatelet/anticoagulant treatment was administered (acetylsalicylic acid, clopidogrel, abciximab, and heparin). In all cases early angiographic control (1–12 days after AMI) showed disappearance of thrombus, no significant residual stenosis, and normal flow. No deterioration of left ventricular function was observed and the clinical course both in hospital and at five months' follow up was uneventful.